The Level of Community Compliance in Ponorogo Regency With The Covid 19 Health Protocol - Latif Setyo Nugroho (Syiah Kuala Law Journal, 2021)
This article discusses the level of community compliance in Ponorogo district with the Covid-19 health protocol. The Covid 19 pandemic has spread on a global scale. This has implications for many sectors. In Indonesia itself has implemented the Health Protocol in every region in the regency and city. No exception in Ponorogo which also applies the health protocol. Health protocols include wearing a mask when traveling, maintaining distance and washing hands after traveling. Many impacts were felt during this pandemic. One of them is felt by traders who usually trade in the Car Free Day area who cannot sell because CFDs are eliminated. In addition, the implementation of a curfew where after 8:00 p.m. the street lights will be turned off and traders selling on the side of the road are required to close. This has led to the turnover of traders who usually open roadside stalls, especially those. even so there are still many who violate these health protocols. One of them can be seen during mask raids on motorists on the highway. The method used is descriptive qualitative method, while the theory used is the conflict of Karl Marx due to differences in interests between society and the government.